A further fragment of early Christian sculpture from St Mary of the Rock, St Andrews, Fife - Kenworthy, J B (Proceedings of the Society of Antiquaries of Scotland, 1981)
A fragment of relief carving depicting an animal head biting the tail of a double outlined ribbon body; stylistic analysis suggests a close relationship with the Durham school of sculpture in the 11th century AD. A R